MENINGKATKAN PEMAHAMAN PESERTA DIDIK MELALUI PEMBELAJARAN REMEDIAL METODE TUTOR SEBAYA PADA MATA PELAJARAN MATEMATIKA DI KELAS XII MIA 3 MAN 2 TANAH DATAR TAHUN PELAJARAN 2018/2019 - Diana, Pesma; Fitriza, Rozi (Math Educa Journal, 2019)
This research is focusing on the efford to enhance students’s understanding, especially for those who have not complete the minimum mark attainment, through peer teaching remedial learning  at 12th Natural Science 3 class, academic year 2018/2019. This is an action class research. Data in this research are qualitative dan quantitative. Qualitative data were gained throughobservation towards students’s activities during peer theaching remedial learning process and through interview. While quantitative data were gathered from daily score and from the test after treatment finishing. The result of the research showed that there is an improvement of students’s understanding through the peer teaching activity. It is showed by the higher percentage of students’s who could reach the minimum score attainment in one basic competence, and it was revealed that students were more active and enthusiastic to ask questions and explanations to their while the remedial teaching took place.